Streptococcus pyogenes: Virulence factors and Prevention measures - Aldilami, Mohammad (Journal of King Abdulaziz University: Science, 2024)
Group A streptococcus, or GAS, is a common name for Streptococcus pyogenes, a significant bacterial pathogen that is particular to humans and can cause a wide range of symptoms, from minor localized infections to potentially fatal invasive infections. The bacterium that causes GAS infections is typically spread by respiratory droplets, skin sores that are touched by GAS, or coming into contact with contaminated objects or materials. Foodborne transmission is another possibility, but further investigation is required to determine the extent of this infection route. It was discovered that GAS illnesses are quite common in indigenous groups, low-socioeconomic areas in developed countries, and emerging countries. Many of the extracellular secretions produced or released by S. pyogenes strains are virulence factors because they aid in the promotion of illness and/or the pathogen's survival in the host. The virulence factors that are released or secreted from the bacterial surface are reviewed in this article. Numerous virulence factors have the potential to serve as digestive enzymes, supplying the bacteria with nutrients derived from the host. Overcrowding and the increased degree of social interaction in these environments have been attributed to this. Improving living conditions and hand and personal cleanliness should be the main goals of prevention and control strategies. In high-risk environments, adherence to infection prevention and control measures should be prioritized. It is also important to consider how governments, particularly those in industrialized nations, distribute resources.